2016
DOI: 10.1016/j.jaubas.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antibacterial activity of nanocrystalline Mn doped Fe2O3 thin films grown by successive ionic layer adsorption and reaction method

Abstract: Successive ionic layer adsorption and reaction (SILAR) method have been successfully employed to grow nanocrystalline Mn doped a-Fe 2 O 3 thin films onto glass substrates. The structural analysis revealed that, the films are nanocrystalline in nature with rhombohedral structure. The optical studies showed that a-Fe 2 O 3 thin film exhibits 3.02 eV band gap energy and it decreases to 2.95 eV as the Mn doping percentage in it was increased from 0 to 8 wt.%. The SILAR grown a-Fe 2 O 3 film exhibits antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The antibacterial activity of the α-Fe2O3 layers was studied against S. aureus bacteria. Their results showed that the antibacterial efficiency for the pure hematite film is 16.66% which is in agreement with the results of this study [55].…”
Section: -5-antibacterial Activitysupporting
confidence: 92%
“…The antibacterial activity of the α-Fe2O3 layers was studied against S. aureus bacteria. Their results showed that the antibacterial efficiency for the pure hematite film is 16.66% which is in agreement with the results of this study [55].…”
Section: -5-antibacterial Activitysupporting
confidence: 92%
“…39 The smaller primary particles have large surface free energy and tend to agglomerate, coalesce, and grow into larger grains. 17,40 The rotationcoalescence of neighboring grains results in elimination of grain boundaries between them and supposedly grain growth. Therefore, grain growth upon anodization is expected to reduce recombination rate of holes and electrons and subsequently enhance conductivity of the photoelectrode.…”
Section: Discussionmentioning
confidence: 99%
“…The films have an optical band gap of 2.95–3.02 eV as the Mn doping percentage varies from 8 to 0%. Both antibacterial activity and optical properties of the thin film increases with Mn doping impling that Mn in α-Fe 2 O 3 can be tuned for biobased optoelectronic devices …”
Section: Prospect Of the Next-generation Devices Based On Iron Oxide ...mentioning
confidence: 99%